Descriptive Analysis on Green Campaign - Damayanti Maulidia; Geodita Woro Bramanti; Santy Dwi Cempaka (International Journal of Business and Management Technology in Society, 2023)
Purpose – This study investigates the effect of green campaigns on green purchase behavior among female consumers of a cosmetic franchise in Surabaya. The campaign encourages customers to return used packaging as a form of environmental responsibility. Methodology – A descriptive analysis was conducted using data from 140 female respondents in Surabaya who were aware of the campaign and had made purchases in the last six months. Data were collected through online questionnaires and analyzed using SPSS, focusing on the constructs of the Theory of Planned Behavior: attitude, subjective norm, and perceived behavioral control. Findings – The results indicate that consumers have a positive attitude toward the campaign and show a high level of perceived behavioral control, meaning they feel capable of engaging in green behavior. However, subjective norm scored lower, suggesting limited social pressure to act sustainably. Overall, the campaign was effective in encouraging pro-environmental purchase behavior. Originality – This study highlights the importance of clear and targeted green campaigns in influencing sustainable consumer behavior. By applying the Theory of Planned Behavior, it offers insights into how companies can enhance the impact of environmental initiatives in the beauty industry.